1995
DOI: 10.1093/clinids/21.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Zaldaride Maleate (a New Calmodulin Antagonist) Versus Loperamide in the Treatment of Traveler's Diarrhea: Randomized, Placebo-Controlled Trial

Abstract: The present study was undertaken to compare the efficacy of a new calmodulin antagonist, zaldaride maleate, with that of placebo or loperamide in persons with traveler's diarrhea. One hundred seventy-nine patients were randomized to receive loperamide (4 mg followed by 2 mg after each unformed stool), zaldaride maleate (20 mg four times per day), or placebo. During the initial 48 hours of therapy, zaldaride maleate decreased the number of unformed stools by 30% and the duration of illness by 23% when compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Zaldaride is a calmodulin-inhibiting drug that has antisecretory properties related to intracellular concentrations of calcium ( 100 ). Th e drug signifi cantly shortened the stools passed in subjects studied with TD compared with placebo therapy ( 96,101,102 ). Racecadotril, a specifi c enkephalinase inhibitor that prevents degradation of the endogenous antisecretory peptide neurotransmitter enkephalins that inhibit cyclic nucleotide secretory pathways without eff ect on gut motility ( 103 ) and has been used successfully in pediatric diarrhea ( 104 ).…”
Section: Recommendationmentioning
confidence: 99%
“…Zaldaride is a calmodulin-inhibiting drug that has antisecretory properties related to intracellular concentrations of calcium ( 100 ). Th e drug signifi cantly shortened the stools passed in subjects studied with TD compared with placebo therapy ( 96,101,102 ). Racecadotril, a specifi c enkephalinase inhibitor that prevents degradation of the endogenous antisecretory peptide neurotransmitter enkephalins that inhibit cyclic nucleotide secretory pathways without eff ect on gut motility ( 103 ) and has been used successfully in pediatric diarrhea ( 104 ).…”
Section: Recommendationmentioning
confidence: 99%
“…It was evaluated in phase III randomized controlled trials in which effi cacy was demonstrated. However, future development was discontinued because of no additional benefi t compared with standard antidiarrheal agents [75,76] . In addition, there was evidence that zaldaride had some unwanted cardiovascular effects when used at the upper end of the therapeutic dosage range for acute diarrhea.…”
Section: Calcium-calmodulin Antagonistsmentioning
confidence: 99%
“…Other ‘purely antisecretory’ agents for treatment of TD include zaldaride maleate (a potent and selective calmodulin inhibitor) [36] and racecadotril (an enkephalinase inhibitor) [37]. Both these compounds are devoid of any effect on gastrointestinal motility and their use is not followed by treatment-related rebound constipation.…”
Section: Treatmentmentioning
confidence: 99%